Empowering sustainability: Can women engineers play a key role in achieving a sustainable future? - Mantoura Nakad; Husni Charif; Linda Gardelle; Rami J Abboud (Sustainable Futures, 2025)
Engineers are considered key professionals and the main driver for achieving the United Nations 17 Sustainable Development Goals (SDGs). Despite this, engineering has long been thought to be man’s job, leading to persistent gender disparity in the profession. This study aims to gain a nuanced understanding of gender differences, if any, in engineers’ awareness and attitudes towards sustainable development (SD). It aims to assess students' perceptions regarding the importance of sustainability and obstacles to SD. It also examines their views on sustainable practices, design projects, university encouragement, campus initiatives, and the role of engineers in advancing sustainability. A structured online survey, consisting of closed-ended questions, was designed to evaluate students’ knowledge and perceptions of sustainability and to identify meaningful differences between male and female students in the field of engineering using the Faculty of Engineering, at the University of Balamand, in Lebanon. The results show that female engineering students scored higher than their male peers with two aspects being of statistical significance related to SD importance. Moreover, female students demonstrated a stronger awareness of SD related challenges and placed greater emphasis on the social pillar of sustainability. These findings highlight the critical importance of encouraging more women to pursue engineering studies and remain active in the profession. Empowering women in engineering can contribute meaningfully to sustain the engineering profession by diversifying it, and by shaping a more sustainable and equitable world.